Autobiographical memory in Alzheimer’s disease: a systematic review - Stramba-Badiale, Chiara; Frisone, Fabio; Biondi, Diana; Riva, Giuseppe (Frontiers in Neurology, 2025)
IntroductionAutobiographical memory impairment is a significant feature of Alzheimer’s disease (AD), affecting patients’ ability to recall personal life events and maintain their sense of self. While this impairment has been extensively studied, its aspects and manifestations remain incompletely synthesized in the literature regarding the relationship between memory specificity, temporal gradients, and emotional processing.MethodsWe conducted a systematic review following PRISMA guidelines, searching across PubMed, Scopus, ScienceDirect, and Web of Science databases. Studies comparing autobiographical memory performance between AD patients and healthy controls were included. Quality assessment used Yang’s methodological checklist to evaluate potential bias in the selected studies. The review process involved independent analysis by two reviewers who assessed titles, abstracts, and full papers against predefined inclusion criteria.ResultsAnalysis of 83 studies revealed consistent autobiographical memory deficits in AD patients. These deficits were characterized by reduced memory specificity across all life periods, with patients showing a tendency toward overgeneralization. The studies demonstrated altered temporal gradients, with remote memories showing better preservation than recent ones, supporting Ribot’s law. Emotional processing patterns were also modified, with some studies indicating a positivity bias in memory recall. Various stimuli showed differential effectiveness in memory retrieval, with music and odors demonstrating particular promise compared to other cues. Neural correlates indicated involvement of hippocampal, prefrontal, and posterior cortical regions in autobiographical memory deficits. The research revealed significant correlations between autobiographical memory performance and executive function measures. Despite memory impairment, evidence suggested preserved components of self-reference.DiscussionThe findings suggest that autobiographical memory impairment in AD affects multiple cognitive domains and impacts patients’ sense of self and quality of life. The identified patterns of impairment and preservation offer potential therapeutic targets and diagnostic markers. These results emphasize the need for standardized assessment protocols for autobiographical memory in AD and suggest the importance of developing targeted interventions leveraging preserved memory systems. The integration of multiple stimulus modalities in memory rehabilitation appears promising. The relationship between autobiographical memory and self-identity maintenance warrants further investigation. The review also highlights the importance of early detection and intervention in autobiographical memory deficits as potential markers of disease progression.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024596837.